Impact of retort process on characteristics and bioactivities of herbal soup based on hydrolyzed collagen from seabass skin - Benjakul, Soottawat (J Food Sci Technol, 2018)
Impact of retort processing on the characteristics and bioactivity of herbal soup, based on hydrolyzed collagen from seabass fish skins, as sterilized health drink in glass bottles, was investigated. Retort processing was conducted at either 115 °C or 121 °C for 5, 7, 9 or 11 min (F(0) values) and compared to no retort processing. All retort processing conditions yielded sterile soups, but some differences in moisture content, pH, viscosity, UV-absorbance, browning index, fluorescence intensity, color, α-amino group and total reducing compound contents were observed, compared to those without retort processing. Retort processing enhanced antioxidative activity of herbal hydrolyzed collagen (HHC) soups, regardless of conditions. HHC soups with F(0) value of 7 at 115 °C (115/7) and 121 °C (121/7) showed significantly higher ABTS and DPPH radical scavenging activities, ferric reducing antioxidant power and H(2)O(2) scavenging activity, compared to others. Retort processing had no significant (p > 0.05) effect on the appearance, color, odor, viscosity, flavor, taste and overall perception of HHC soups. The 115/7 and 121/7 samples stimulated cell proliferation and enhance collagen production of L929 mouse fibroblast cells. It was therefore concluded that retort processing could be used for preparing sterilized HHC soup as a ready-to-serve functional drink that is both healthy and safe.